Comparative Evaluation of Complex Treatment of Peri-Implantitis According to Cytological Studies (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The study involved 66 patients who underwent dental implantation. In the main group, local ozone therapy was included in the complex treatment. A cytological study of neutrophilic leukocytes and epithelial cells in saliva was performed. It was noted that in the main group after ozone therapy, the content of neutrophilic leukocytes and epithelial cells in saliva sharply decreased, approaching normal levels.